2018
DOI: 10.1111/ijlh.12933
|View full text |Cite
|
Sign up to set email alerts
|

Hidden myelodysplastic syndrome (MDS): A prospective study to confirm or exclude MDS in patients with anemia of uncertain etiology

Abstract: Introduction Diagnosis of myelodysplastic syndromes (MDSs) when anemia is the only abnormality can be complicated. The aim of our study was to investigate the primary causes of anemia and/or macrocytosis of uncertain etiology. Methods We conducted a multicenter, prospective study over 4 months in three hematology laboratories. In step 1, we used an automated informatics system to screen 137 453 hemograms for cases of anemia and/or macrocytosis (n = 2702). In step 2, we excluded all patients whose anemia appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Patients may present with severe neurologic features and an elevated lactate dehydrogenase (LDH) with fragmented RBCs, concerning for thrombotic thrombocytopenic purpura (TTP), 14,15 or may have severe pancytopenia with bone marrows showing hypercellularity and morphologic atypia, raising concern for myelodysplastic syndrome (MDS) or even acute leukemia. 16 Consequently, the diagnosis of MA can be missed in some cases, as features can be quite complex and heterogeneous, and vitamin B 12 concentrations may not factor into initial workups given nonspecific symptomatology. In addition, issues may arise in laboratory testing including false normal cobalamin concentrations, adding to this diagnostic challenge.…”
Section: Overviewmentioning
confidence: 99%
“…Patients may present with severe neurologic features and an elevated lactate dehydrogenase (LDH) with fragmented RBCs, concerning for thrombotic thrombocytopenic purpura (TTP), 14,15 or may have severe pancytopenia with bone marrows showing hypercellularity and morphologic atypia, raising concern for myelodysplastic syndrome (MDS) or even acute leukemia. 16 Consequently, the diagnosis of MA can be missed in some cases, as features can be quite complex and heterogeneous, and vitamin B 12 concentrations may not factor into initial workups given nonspecific symptomatology. In addition, issues may arise in laboratory testing including false normal cobalamin concentrations, adding to this diagnostic challenge.…”
Section: Overviewmentioning
confidence: 99%
“…30 Bastida JM et al, studied patients with anemia of uncertain etiology and found hematologic disorders in 25 patients of which 14 were diagnosed with MDS. 31 In this study, MDS was diagnosed in 3 patients and aplastic anemia in one patient. Multifactor etiology is frequently found as causation of anemia and Petrosyan I et al, reported 46.3% of patients having anemia of multifactorial etiology in their study.…”
Section: Discussionmentioning
confidence: 77%
“…Mostly, alterations in these values occur due to deficiency anemia, kidney neoplasms, and medullar dysplasia. 45,46 According to what has been thoroughly demonstrated and discussed here, chronic physical exercise resulted in increased BDNF in blood plasma of trained diabetic animals, which promoted significant improvement of the metabolic syndrome related to DM. This physiological condition with a good prognosis, possibly associated with the increase in this factor, could be verified by significant alterations in biochemical and hematological profiles that resulted in physiological improvement of the organism against harmful effects of diabetes mellitus.…”
Section: Erythrogram Evaluationmentioning
confidence: 80%